THE DEVELOPMENT OF A 5W + 1H BASED POCKET BOOK ON THE KINGDOMS HISTORY MATERIAL TO IMPROVE READING LITERACY OF GRADE 4 ELEMENTARY STUDENTS - Laila Fatmawati; Subkhi Fajrikah (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2019)
Abstract. This research was motivated by the problems found in elementary schools, which are students’ low literacy ability and lack of supporting books in learning. This research aimed to develop pocket book teaching material, determine the feasibility and the effectiveness of the 5W + 1H based pocket book on the kingdoms history material to improve reading literacy in the fourth grade elementary school students. The Development Procedure used the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Small group trial subjects were 10 students from grade IV Shidiq and large group trials were 28 students from grade IV Amanah. While the operational field trial were conducted on 30 students from grade IV Fatonah and Tabligh. The results of the research on the feasibility test of media expert got a score of 78,91 with the category of